2011
DOI: 10.1017/s1751731110002193
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, digestibility and faecal coliform bacteria in weaned piglets fed a cereal-based diet including either chicory (Cichorium intybus L) or ribwort (Plantago lanceolata L) forage

Abstract: Twenty-five weaned 35-day-old piglets were used in a 35-day growth experiment to evaluate the effect of inclusion of chicory and ribwort forage in a cereal-based diet on growth performance, feed intake, digestibility and shedding of faecal coliform bacteria. A total of seven experimental diets were formulated, a cereal-based basal diet (B), and six diets with inclusion of 40, 80 and 160 g/kg chicory (C40, C80 and C160) or ribwort (R40, R80 and R160). Piglets had ad libitum access to feed and water throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 24 publications
3
36
0
2
Order By: Relevance
“…Inclusion of 80 g/kg chicory forage or root did not impair the CTTAD of OM or energy, and inclusion of 160 g/kg only gave minor impairment of the same parameters, whereas the CTTAD of NSP, especially uronic acids, increased with increased chicory forage inclusion, which is in agreement with a previous study (Ivarsson et al, 2011). This can be explained by differences in chemical composition of the plant cell walls between the fibre sources compared in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Inclusion of 80 g/kg chicory forage or root did not impair the CTTAD of OM or energy, and inclusion of 160 g/kg only gave minor impairment of the same parameters, whereas the CTTAD of NSP, especially uronic acids, increased with increased chicory forage inclusion, which is in agreement with a previous study (Ivarsson et al, 2011). This can be explained by differences in chemical composition of the plant cell walls between the fibre sources compared in this study.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous studies where chicory forage and inulin have been included in diets of weaned piglets (Halas et al, 2009;Ivarsson et al, 2011). It should be noted that these studies have used few animals per treatment in short-term experiments, and to fully explore the potential of chicory feeding on growth performance long-term feeding trials need to be performed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, it is considered to be an important economic plant with extreme potential for future development (Bais and Ravishankar, 2001;de Kraker et al, 2001;Sulas, 2004;Nandagopal and Kumari, 2007). As forage, chicory is rich in nutrition, yields, palatability, digestibility, resistance to adversity, and pest resistance (de Kraker et al, 2002;Sulas, 2004;Ivarsson et al, 2011). Research has shown that the nutrition of chicory is virtually equivalent to and even surpasses some varieties of alfalfa (Sulas, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These substrates, commonly referred to as prebiotics, can alter gut bacterial composition, modify intestinal fermentation processes, promote gut development, and possibly improve host health (9). Chicory (Cichorium intybus L.) is a perennial herb that can be used as a fiber source in pig diets (17). Chicory root, which has a high content of inulin-type fructan and oligofructose, is a prototype prebiotic for monogastrics (32).…”
mentioning
confidence: 99%